PPDPF Promotes the Development of Mutant KRAS‐Driven Pancreatic Ductal Adenocarcinoma by Regulating the GEF Activity of SOS1. Issue 2 (1st December 2022) - Ni, Qian‐Zhi; Zhu, Bing; Ji, Yan; Zheng, Qian‐Wen; Liang, Xin; Ma, Ning; Jiang, Hao; Zhang, Feng‐Kun; Shang, Yu‐Rong; Wang, Yi‐Kang; Xu, Sheng; Zhang, Er‐Bin; et al.
Abstract: The guanine nucleotide exchange factor (GEF) SOS1 catalyzes the exchange of GDP for GTP on RAS. However, regulation of the GEF activity remains elusive. Here, the authors report that PPDPF functions as an important regulator of SOS1. The expression of PPDPF is significantly increased in pancreatic ductal adenocarcinoma (PDAC), associated with poor prognosis and recurrence of PDAC patients. Overexpression of PPDPF promotes PDAC cell growth in vitro and in vivo, while PPDPF knockout exerts opposite effects. Pancreatic‐specific deletion of PPDPF profoundly inhibits tumor development in KRAS G12D ‐driven genetic mouse models of PDAC. PPDPF can bind GTP and transfer GTP to SOS1. Mutations of the GTP‐binding sites severely impair the tumor‐promoting effect of PPDPF. Consistently, mutations of the critical amino acids mediating SOS1–PPDPF interaction significantly impair the GEF activity of SOS1. Therefore, this study demonstrates a novel model of KRAS activation via PPDPF‐SOS1 axis, and provides a promising therapeutic target for PDAC. Abstract : This study reveals a novel model of KRAS activation via PPDPF‐SOS1 axis. PPDPF is upregulated in pancreatic ductal adenocarcinoma. It can bind GTP and offer GTP to SOS1, which stimulates the GEF activity of SOS1 and subsequent activation of KRAS. This work provides a promising therapeutic target for PDAC.